A survey on load balancing algorithms in cloud computing. (2017) - Khan, Rafiqul Zaman; Ahmad, Mohammad Oqail
Cloud computing is a rising technology, which offers various online services like data storage, application and infrastructure on pay per used fashion that provides access in location independent manner. These services offer significant benefits for both consumer and producer. For optimal utilisation of resources, researchers from both academia and industry focus their efforts towards on cloud computing services. To achieve this target, numerous challenges have to be faced, out of which, load balancing is a centric issue in cloud computing environment which requires distribution of work load in a fairly manner across all the nodes. In this paper, a rich collection of algorithms has been surveyed and presented with detailed classification of algorithms based on different metrics such as reaction time, resource utilisation and energy efficiency and so on. Moreover, the merits, demerits, implementation tool and scope of implementation of each algorithm have been presented. The different implementation tools have also been discussed which provides the better idea for simulation platform. This work is intended to enable the readers to decide suitable approach and simulation platform for better load balancing algorithm.